Identifying and prioritizing concerns associated with prosthetic devices for use in a benefit-risk assessment: a mixed-methods approach. (4th May 2018) - Janssen, Ellen M; Benz, Heather L; Tsai, Jui-Hua; Bridges, John FP
ABSTRACT: Objective : We identified and prioritized concerns reported by stakeholders associated with novel upper-limb prostheses. Methods : An evidence review and key-informant engagement, identified 62 concerns with upper-limb prostheses with implantable components. We selected 16 concerns for inclusion in a best-worst scaling (BWS) prioritization survey. Focus groups and BWS were used to engage stakeholders at a public meeting on prostheses. In 16 BWS choice tasks, attendees selected the most and least influential concern when choosing an upper-limb prosthesis. Aggregate data were analyzed using choice frequencies and conditional logit analysis. Latent class analysis examined heterogeneity in priorities. Estimates were adjusted to importance ratios which indicate how influential each concern is in the decision making process. Results : Forty-seven (47) stakeholders from diverse backgrounds completed the BWS survey (response rate 51%). On aggregate, the most influential concern was reliability of the device (importance ratio: 13%), and least influential was the concern of an outdated device (importance ratio: 1%). Latent class analysis identified two classes with approximately 50% of participants each. The first class was most influenced by effectiveness of the device. The second class was most influenced by minimizing risks. Conclusion : In this pilot, we identified heterogeneity in how participants prioritize concerns for upper-limb prostheses.